(untitled) (Journal Of Educational and Psychological Researches, 2022)
Technology plays a vital role in all walks of life, one of these is Education. Google Classroom is one of the educational tools that are free of cost and recently has gained popularity within a short period in many countries, including Iraq. The primary purpose of this study is to explore the Google Classroom use in EFL learners’ composition writing. The sample of the study is EFL Second-year College students from the College of Science for Women /Computer Science Department, which consisted of (35) students who have implemented Google Classroom for at least one semester in their classroom. The students were asked to finish two uncompleted paragraphs that have the only main idea and write a suitable conclusion to each one. The results showed that Google Classroom is not an entirely effective application in developing student’s achievements in composition writing, but it is useful.